2019
DOI: 10.1016/j.jalz.2019.06.1166
|View full text |Cite
|
Sign up to set email alerts
|

P1‐561: Hospitalisation Rates and Predictors in People With Dementia: A Systematic Review And meta‐analysis

Abstract: Background: Hospitalisation is often harmful for people with dementia and results in high societal costs, so avoidance of unnecessary admissions is a global priority. However, no intervention has yet reduced admissions of community-dwelling people with dementia. We therefore aimed to examine hospitalisation rates of people with dementia and whether these differ from people without dementia and to identify socio-demographic and clinical predictors of hospitalisation. Methods: We searched MEDLINE, Embase, and Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Evidence suggests that the majority of hospitalised patients in Ghana are older adults (Narh et al, 2021) with age‐related functional impairments and chronic health conditions (Amegbor & Rosenberg, 2020). Using a meta‐analytic approach, Sommerlad et al (2019) identified age‐related multimorbidity and lower functional ability as risk factors for hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence suggests that the majority of hospitalised patients in Ghana are older adults (Narh et al, 2021) with age‐related functional impairments and chronic health conditions (Amegbor & Rosenberg, 2020). Using a meta‐analytic approach, Sommerlad et al (2019) identified age‐related multimorbidity and lower functional ability as risk factors for hospitalisation.…”
Section: Introductionmentioning
confidence: 99%
“…Older adults remain the major consumers of healthcare services because of a range of physical and psychological comorbidities associated with ageing (Sommerlad et al, 2019; Van den Heede et al, 2019). In 2014, older adults (≥75 years) constituted only 9% of Belgium's population, but accounted for more than 25% of all hospitalisations (Van den Heede et al, 2019).…”
Section: Introductionmentioning
confidence: 99%